EIS Characteristics of Galvanic Couple of Aluminum Alloy and High-strength Steel under Thin Solution Films. Issue 13 (5th October 2020) - Tran, Van Nam; Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : Galvanic corrosion of 6061-T6 (AA) coupled with high-strength steel (HSS) under 2 M NaCl solution films was investigated by electrochemical impedance spectroscopy (EIS). The AA is passivated in a 2 M NaCl solution and suffered pitting corrosion by galvanic coupling with HSS of the same surface area. Impedance of the AA/HSS couple was successfully measured under thin solution films (25–100 μ m) using a potentiostat as a zero-resistance ammeter. The obtained impedance data shows a typical transmission line behavior above 1 kHz, owing to a nonuniform current distribution. Impedances for the AA and HSS were separately measured in the frequency domain. The average growth rate of pits on the AA surface, estimated from the charge transfer resistance for AA, increased with decreasing solution film thickness.